The Influence of Entrepreneurial Attitude and Motivation on the Success of Community Enterprises in the Rankiang Saiyo Cooperative, Tanah Datar Regency - Imran; Lukito, Hendra Lukito; Rustam, Zulli Rustam; Raihani, Hulfa (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
Cooperatives play an important role in supporting economic development, especially in rural Indonesia. This study aims to analyse the impact of entrepreneurial attitudes and motivation on business success and evaluate the management effectiveness of Rangkiang Saiyo Cooperative, which has achieved assets of IDR 1.2 billion and won various awards at the provincial and district levels. The method used in this study is a quantitative approach with a survey of cooperative members supported by descriptive and inferential analyses. The results show that the entrepreneurial attitude and motivation of co-operative members have a significant influence on the success of their businesses. In addition, entrepreneurship training is proven to improve members' skills and productivity, although there are still obstacles such as suboptimal utilisation of the grants. The research also highlights the importance of strengthening social capital, financial product innovation, and cooperative empowerment strategies to improve organisational sustainability and efficiency. The findings provide recommendations for the development of cooperatives as drivers of the local economy in Indonesia.